Determinants of Female Entrepreneurial Success: The Influence of Social, Financial, and Institutional Support - Rahmatullah Pashtoon; Noorihsan Bin Mohamad; Zarinah Hamid (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2025)
Purpose: This research aims to identify the variables that impact both the financial and non-financial performances of Afghan women-owned businesses.Method: This study utilized a descriptive, cross-sectional design with a quantitative approach, employing a Structural Equation Model (SEM) to assess the influence of push and pull factors on the success of female entrepreneurs. A purposive sample of 308 women-led Micro and Small Enterprises (MSEs) in Kandahar, Afghanistan, was surveyed using a structured questionnaire.Result: The study identified key determinants influencing both the financial and non-financial performance of women entrepreneurs. Significant factors include familial support and motivation, access to financial resources, availability of training and professional development opportunities, and support from governmental and non-governmental organizations. Conversely, self-independence, self-efficacy, and access to professional networks did not exhibit a statistically significant positive impact on business performance.Practical Implications for Economic Growth and Development: This article outlines key strategies for enhancing the business environment and success of female entrepreneurs. The findings provide a basis for policymakers to design supportive frameworks that foster the growth and sustainability of women-led enterprises. By identifying critical success factors, the study contributes to the empowerment of female entrepreneurs and their transformative role in driving innovation, job creation, economic development, and poverty alleviation.Originality/Value: Although there is ample research on female entrepreneurs, a notable gap exists in studies that explicitly examine the factors influencing their financial and non-financial success, particularly in war-torn areas such as Kandahar. This paper explores significant topics and advocates for further investigation in this field.